Energetic materials encyclopedia. - Klapötke, Thomas M. (Energetic Materials Encyclopedia ;, 2021)
The Energetic Materials Encyclopedia is a compendium of pure energetic materials (i.e., not formulations) which summarizes the most important parameters of these compounds. The impact, friction and electrostatic discharge (ESD) sensitivity parameters are reported. Thermal parameters such as the melting points and decomposition temperatures are also given together with the thermodynamic enthalpies of formation. The density values that govern the detonation performance are given for the theoretical maximum density (TMD) and, where appropriate, also for lower densities. The most important performance parameters such as the detonation pressure, the detonation velocity as well as the temperature of explosion and the heat of explosion are also stated. Wherever possible experimental values are given together with calculated parameters. If multiple values for one property were available from the literature, these are also stated, e.g. 20 different detonation velocities for RDX. For all literature values, the original references have been included. This revised and updated edition of the Energetic Materials Encyclopedia will be of interest to professionals, advanced students and educators in chemistry, materials science, engineering and military technology. All data have been updated and additional compounds not listed in the first edition have been included.